Answer:
x = 11
Explanation:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation:
*(-2-2*x)/(3)-(-8)=0
Simplify:
*-2 - 2x / 3
Pull out like factors:
*-2 - 2x = -2 • (x + 1)
Now It should look like this:
-2 • (x + 1) / 3 - (-8) = 0
Rewrite the whole as a equivalent fraction using 3 as the denominator:
*-8 = -8 / 1 = -8 • 3 / 3
Add the two equivalent fractions which now have a common denominator
-Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:
*-2 • (x+1) - (-8 • 3) / 3 = 22 - 2x / 3
Pull out like factors:
*22 - 2x = -2 • (x - 11)
Now you should have this:
*-2 • (x - 11) / 3 = 0
Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.
-Now, to get rid of the denominator, multiply both sides of the equation by the denominator.
*-2•(x-11) / 3 • 3 = 0 • 3
-Now, on the left hand side, the 3 cancels out the denominator, while, on the right hand side, zero times anything is still zero.
Now you should have this:
*-2 • (x-11) = 0
Now Solve:
x-11 = 0
-Add 11 to both sides of the equation:
x = 11